2013
DOI: 10.1136/jclinpath-2012-201404
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancerdiagnosis in aresource poorenvironment through a collaborativemultidisciplinaryapproach: the Kenyan experience

Abstract: We describe our experience and outcome from the workshop, which can be modelled for other resource poor settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Although SBE and CBE may be the only feasible options in low-resource settings, when combined with education about the early signs and symptoms of breast cancer, these may be important tools to facilitate early detection. 11 However, it is clear that, for a screening program to improve outcomes, an accessible treatment program must also be in place. There are several ways this could be achieved, again ranging from promising nonsurgical options such as ablative techniques to traditional treatments with surgery, chemotherapy, and/or radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Although SBE and CBE may be the only feasible options in low-resource settings, when combined with education about the early signs and symptoms of breast cancer, these may be important tools to facilitate early detection. 11 However, it is clear that, for a screening program to improve outcomes, an accessible treatment program must also be in place. There are several ways this could be achieved, again ranging from promising nonsurgical options such as ablative techniques to traditional treatments with surgery, chemotherapy, and/or radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A critical challenge in the management of LABCs in LMICs is that a large fraction or even majority of these cancers are extremely advanced at presentation with large, ulcerated tumors. In these cases, extensive surgical resection is required to achieve complete removal of gross locoregional disease, even after neoadjuvant chemotherapy 18 . Although the traditional radical mastectomy (removal of the pectoralis muscles as well as the breast and axillary nodes) is rarely performed in high‐income countries today, muscle resection frequently continues to be required in sub‐Saharan Africa and other LMICs when tumors extensively invade the chest wall.…”
Section: Multimodality Breast Cancer Treatment In Lmicsmentioning
confidence: 99%
“…However, the results of some African studies are compatible with the hypothesis that a third factor might be responsible-at least in part-of the molecular characteristics of BC in sub-Saharan Africa, that is, the biases deriving from preanalytical problems with tissue collection and processing, in particular from problems of underfixation or overfixation of surgical specimens. [5][6][7][8] These studies, in which standardised methods for collection, processing and reporting of specimens have been prospectively used, have reported that the frequency of Kenyan, Ethiopian and South African patients with ER-negative BC and triple-negative BC may be comparable with that found among patients from the Western countries. The authors have defined the standardisation of the preanalytic process and the implementation of quality assurance schemes as urgent needs.…”
Section: Correspondencementioning
confidence: 99%
“…6 7 They have also drawn attention to the fact that most African studies reporting a disproportionately high prevalence of patients with ER-negative BC had a retrospective design. 6 To add further evidence to the existing African literature on the relationship between the level of standardisation of the preanalytic process and the distribution by BC subtype, two of us (SB and MP) have reviewed the samples of the original immunohistochemical preparations from the Italian-Tanzanian study. 4 They have found that about one-third of specimens from Tanzania were not evaluable and showed staining artefacts reflecting limitations in fixation and paraffin-embedding procedures.…”
Section: Correspondencementioning
confidence: 99%
See 1 more Smart Citation